High Breakdown Current Density in Quasi-1D van der Waals Layered Material Ta2NiSe7 - Yoon, Sang Ok; Jeon, Jiho; Choi, Kyung Hwan; Jeong, Byung Joo; Chae, Sudong; Kim, Bum Jun; Oh, Seungbae; Woo, Chaeheon; Lee, Bom; Cho, Sooheon; Kim, Tae Yeong; Jang, Han Eol; et al. (ACS Applied Materials and Interfaces, 2021)
We synthesized ternary composition chalcogenide Ta2NiSe7, a quasi-one-dimensional (Q1D) material with excellent crystallinity. To utilize the excellent electrical conductivity property of Ta2NiSe7, the breakdown current density (JBD) according to thickness change through mechanical exfoliation was measured. It was confirmed that as the thickness decreased, the maximum breakdown voltage (VBD) increased, and at 18 nm thickness, 35 MA cm-2 of JBD was measured, which was 35 times higher than that of copper, which is commonly used as an interconnect material. By optimization of the exfoliation process, it is expected that through a theoretical model fitting, the JBD can be increased to about 356 MA cm-2. It is expected that the low-dimensional materials with ternary compositions proposed through this experiment can be used as candidates for current-carrying materials that are required for the miniaturization of various electronic devices.
Keywords: current; Breakdown currents; Current-carrying material; High breakdown; High breakdown material; Layered material; Low-dimensional materials; Ternary chalcogenides; Ternary composition; Van der Waal; current-carrying materials; high breakdown materials; low-dimensional materials; Ta2NiSe7; ternary chalcogenide